Analisis Strategi Marketing Percetakan Cv. Citra Dalam Meningkatkan Penjualan Di Kota Medan - Nadia Masthura; Azhari Akmal Tarigan (Jurnal Ekonomi dan Bisnis Digital, 2022)
This research aims to find out what marketing strategies are used by CV Printing. Medan image to increase sales. The research method used is a qualitative descriptive method where the research is intended to describe the object in the form of a description, namely by going directly to the location, conducting interviews. The research results show that strategies that can be implemented to increase sales include providing relief to customers with the accounts receivable system. In this case CV printing. Citra Medan helps its clients and customers by providing printed goods in advance and paying with an installment system. This is very helpful for Medan Citra Printing partner businesses which generally have minimal capital, such as cake shops and other small traders. Implementation of marketing in CV printing. Citra Medan also has a role in increasing this business so that it develops and progresses, still existing today. So it means that the application of marketing is very successful in bringing CVs. Medan's image is to improve its business through, setting affordable prices for customers with good quality which is used by various groups, middle and even upper class.